Pengaruh Rasio Likuiditas, Rasio Solvabilitas, dan Rasio Aktivitas Terhadap Kinerja Keuangan Perusahaan Suparma Tbk Periode 2019-2023 - M. Fajar Rifki Al Adib; Hartono Hartono; Yuliasnita Verlandes (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
A company is an entity consisting of individuals or groups who work together to achieve certain goals. PT Suparma cannot be separated from businesses that aim to gain profits in generating effectiveness and efficiency in financial management. Financial management or financial performance has an impact on the company. This research aims to determine the effect of liquidity ratios, solvency ratios and activity ratios on the financial performance of PT Suparma tbk for the 2019-2023 period. This research was conducted by calculating the financial ratios of PT Suparma Tbk which is listed on the Indonesia Stock Exchange. The data analysis technique uses multiple linear regression. The research results show that the liquidity ratio calculated using the current ratio has a positive and insignificant effect on financial performance (ROA), the solvency ratio calculated using the debt to equity ratio has a negative and insignificant effect on financial performance (ROA), and the activity ratio calculated using total asset turnover has a positive and significant effect on financial performance.